Association of education level and depression with cognitive decline: findings from the examining cognitive health outcomes in heart failure study - Wleklik, Marta; Lee, Christopher S.; Jędrzejczyk, Maria; Aldossary, Heba; Uchmanowicz, Izabella (Frontiers in Cardiovascular Medicine, 2025)
IntroductionCognitive decline in older adults with heart failure (HF) may be influenced by educational level and depressive symptoms. This study assesses the impact of these factors on cognitive function in this patient population to mitigate cognitive decline and improve overall health in this vulnerable population.AimTo identify the predictors of cognitive impairment in older patients with heart failure using a longitudinal mixed-model analysis.Material and methodsA 250 HF patients aged 60 and older with an MMSE score ≥24 was evaluated. Cognitive function was assessed using the Mini-Mental State Examination (MMSE), mental health with the Hospital Anxiety and Depression Scale (HADS) and Patient Health Questionnaire-9 (PHQ-9), and nutritional status with the Mini Nutritional Assessment (MNA). Data were collected in three stages: baseline during hospitalization and at two subsequent hospital follow-ups. A linear mixed model analyzed the relationship between educational level, depressive symptoms, and MMSE scores, with a significance level set at p < 0.05.ResultsThe mean baseline MMSE score was 26.5 (SD = 2.1), suggesting good initial cognitive function among participants. Results from the linear mixed model indicated that each additional year of education correlated with a 0.161-point increase in MMSE scores (95%CI: 0.1–0.222, p < 0.001). Conversely, higher depressive symptoms were associated with poorer cognitive outcomes; specifically, each one-point increase in the HADS depression subscale corresponded to a 0.115-point decrease in MMSE scores (95%CI: −0.183 to −0.046, p = 0.001). Other factors, including age, sex, residence, and various comorbidities, did not show statistically significant associations with cognitive decline. At each stage of the study, approximately 8%, 11%, and 11% of patients, respectively, scored above the HADS cut-off for anxiety or depression, while an additional 13%, 12%, and 15% showed borderline scores. According to the PHQ-9, depressive symptoms of varying severity were present in 54% of patients at Stage I and II, and in 58% at Stage III.ConclusionsThis study shows that greater educational background is associated with improved cognitive function, while higher levels of anxiety and depression are linked to cognitive decline in older adults with heart failure. These results highlight the importance of integrating mental health and education in interventions aimed at enhancing cognitive health in this population.